Diagnostic performance of susceptibility-weighted magnetic resonance imaging for the assessment of sub-coracoacromial spurs causing subacromial impingement syndrome - Noerenberg, Dominik; Armbruster, Marco; Bender, Yi-Na; Walter, Thula; Ebersberger, Hans U.; Diederichs, Gerd; Hamm, Bernd; Ockert, Ben; Makowski, Marcus R. (European Radiology, 2017)
Objectives: To evaluate the potential of susceptibility-weighted-magnetic-resonance-imaging (SWMR) for the detection of sub-coracoacromial spurs in patients with clinically suspected subacromial impingement syndrome (SAIS), compared to standard MR-sequences and radiographs. Methods: Forty-four patients with suspected SAIS were included. All patients underwent radiography, standard MRI of the shoulder and SWMR. Radiograph-based identification of sub-coracoacromial spurs served as goldstandard. Radiographs identified twenty-three spurs in twenty-three patients. Twenty-one patients without spur formation served as reference group. Detection rate, sensitivity/specificity and interobserver-agreements were calculated. Linear regression was applied to determine the relationship between size measurements on radiographs and MRI. Results: Detection rates for spurs on standard MRI and SWMR were 47.8 % and 91.3 % compared to radiography (p<0.001). SWMR demonstrated a sensitivity of 97.7 % (CI=0.92-1) and a specificity of 91.3 % (CI=0.788-1) for the identification of spurs. Standard MR-sequences achieved a sensitivity of 47.8 % (CI=0.185-0.775) and a specificity of 80.8 % (CI=0.642-0.978). Size measurements between SWMR and radiography showed a good correlation (R2=0.75;p<0.0001), while overestimating lesion size (5.7±1.2 mm; 4.3±1.3 mm;p<0.0001). Interobserver-agreement for spurs was high on SWMR (R2=0.74;p<0.0001), but low on standard MRI (R2=0.24;p<0.0001). Conclusions: SWMR allows a reliable detection of sub-coracoacromial spur formation in patients with SAIS and is superior to standard MR-sequences using radiography as goldstandard. Key Points: • SWMR has the potential to reliably identify sub-coracoacromial spurs without radiation exposure. • SWMR provides comparable detection rates to conventional radiography for sub-coracoacromial spur formation. • SWMR yields higher detection rates compared to standard-MR regarding sub-coracoacromial spur formation. • SWMR can be implemented in routine shoulder MRI protocols.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Acromioclavicular joint; Magnetic resonance imaging; Sub-coracoacromial spur; Subacromial impingement; Susceptibility-weighted MR imaging